SUKSES MEMBUKA ONLINE UNTUK MEMBANGUN DAN PENGEMBANGAN USAHA KECIL BAGI MASYARAKAT PERKOTAAN - Nina Adelina; Wagiyem Wagiyem (STIE Atma Bhakti, 2022)
The use of the internet that is in demand and is increasing every year is a reference for making online sales efforts. After conducting research, tracing and observing from the internet network, there are still not many business players who come from women and women's groups in general, giving rise to opportunities for this flexible business. Online business business training in Kampung Calen RT 02 RW 04 Bendosari Sukoharjo aims to improve an online business that has been carried out by 10 women in this village, and provides an understanding of online business opportunities. The training was attended by 45 women in this village, using the Forum Discussion Group (FGD) method. The result of this training is that participants participate enthusiastically and follow up by making their sales display on social media even better. Keywords: Online Business, Culinary, Fashion, Markerplace, Digital